Preface - Niko Pavlopoulos; Luis Viveros Montoya; Conor Crummey; Niko Pavlopoulos; Luis Viveros Montoya; Conor Crummey (UCL Journal of Law and Jurisprudence, 2017)
Preface to Voume 6, Issue 1 of the UCL Journal of Law and Jurisprudence. For the full text, please click here